A Ratiometric Photoacoustic Probe with a Reversible Response to Hydrogen Sulfide and Hydroxyl Radicals for Dynamic Imaging of Liver Inflammation. Issue 37 (8th August 2022) - Wu, Luyan; Zeng, Wenhui; Ishigaki, Yusuke; Zhang, Junya; Bai, He; Harimoto, Takashi; Suzuki, Takanori; Ye, Deju
Abstract: Reversible imaging probes that allow for the dynamic visualization of the redox cycle between hydroxyl radical (⋅OH) and hydrogen sulfide (H2 S) are vital to probe the redox imbalance‐involved pathological process in vivo. Herein, we report a reversible ratiometric photoacoustic (PA) imaging nanoprobe (1 ‐PAIN) for the real‐time imaging of ⋅OH/H2 S redox cycle in vivo. 1 ‐PAIN displays a low PA ratio between 690 and 825 nm (PA690 /PA825 ), which significantly increases by ≈5‐fold upon oxidation by ⋅OH, and is switched back to the initially low PA690 /PA825 value upon reduction by H2 S. 1 ‐PAIN could dynamically report on the hepatic ⋅OH production in mice during the lipopolysaccharide (LPS)‐induced liver inflammation process, and visualize hepatic H2 S generation during the N ‐acetyl cysteine (NAC)‐induced anti‐inflammation process. 1 ‐PAIN can act as a useful tool to probe the redox state in living biology, beneficial for the study of redox imbalance‐related diseases. Abstract : A reversible ratiometric photoacoustic (PA) imaging probe is designed, which shows a reversible switch in the PA ratio (PA690 /PA825 ) in response to the redox cycle between ⋅OH and H2 S. The probe allows the non‐invasive and dynamic imaging of the redox fluctuation in mice during lipopolysaccharide (LPS)‐induced liver inflammation and the subsequent N ‐acetyl cysteine (NAC)‐mediated anti‐inflammation process.